Visualization analysis of research progress and trend of fermented grains based on bibliometrics - LI Ke, OUYANG Runkun, SU Yun, HOU Aixiang, LI Jie, LI Zongjun (Zhongguo niangzao)
As the key to microbial fermentation, fermented grains have a decisive influence on the quality and flavor of Baijiu. In recent years, the research on fermented grains has received extensive attention from the academic community, especially in terms of the influence of microbial populations and their metabolic activities on the quality of Baijiu. Based on the bibliometric method, from multiple dimensions such as the number of published articles, journal distribution, author and institutional cooperation network, keywords co-occurrence and cluster analysis, the 1 373 related literatures published on China National Knowledge Infrastructure (CNKI) from 2014 to 2023 were systematically sorted out and visualized using CiteSpace V6.3.R1 software. The aim was to reveal the current hotspots and development trends of fermented grains research. The results showed that the main topics of fermented grains research focus on flavor substances, microorganisms and their fermentation processes, and microorganisms and flavor substances were the hot spots in the field of fermented grains. The study provided important references and guidance for researchers in the field of fermented grains, promoted further exploration and innovation in the field, and advanced the sustainable development of China's fermented grains industry.